Adolescent Dating Violence: Results of a Mixed Study in Quito, Ecuador - Medina Maldonado, Venus Elizabeth (Journal of interpersonal violence, 2022)
Dating violence is a public health problem affecting people worldwide. This study evaluated the occurrence of different types of adolescent dating violence using a mixed analysis of each data source. The present study addresses the following research questions: does the occurrence of the types of violence analyzed in the quantitative phase match with the narratives obtained in the qualitative phase? and does the additional information obtained in the qualitative phase improve the understanding of the analyzed phenomenon?In the quantitative phase, 410 participants (aged 13 to 19 years) answered a questionnaire based on the Modified Conflict Tactics Scale, while in the qualitative phase, 26 participated in two focus groups. Data were collected from May to June 2019. Written informed consent was obtained from the parents or legal guardians of those who had agreed to participate. The present research was approved by the Human Research Ethics Committee of the Pontifical Catholic University of Ecuador. The results were divided on: prevalence of dating violence based on age groups and gender, management and resolution of dating conflicts, victimization and perpetration of intimate partner violence, factors favoring intimate partner violence and acceptance of abuse. The results were analyzed via triangulation and indicated that adolescents were involved in the perpetration and victimization of psychological as well as mild and severe physical violence. An analysis of the contributing factors revealed a strong tendency toward the acceptance of the traditional gender model. Challenging these models is crucial to deconstruct hierarchical models, develop conflict resolution skills, and promptly identify abusive behaviors that affect emotional development. The combination of different methodological approaches improved the understanding of the phenomenon studied.